2014
DOI: 10.4103/2277-9175.124637
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of the thyroid gland volume among 8-15-year-old children in Isfahan, Iran

Abstract: Background:Local reference data are needed in the screening of children for thyroid enlargement. We determined the thyroid gland volume using the ultrasonography (US) in schoolchildren of Isfahan, Iran.Materials and Methods:A total of 360 schoolchildren (59% girls) aged 8-15 years who met the study criteria were entered the study. Clinical grading of goiter was performed by an endocrinologist according to the World Health Organization (WHO) classification. Then, a single expert radiologist performed thyroid vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
9
0
2
Order By: Relevance
“…The WHO has developed criteria for defining TGR in children based on BSA, age, and sex (16,19), whereas the criteria in China were according to age (5). In this study, the Tvol was slightly higher in boys than in girls which is consistent with other studies (10,32,33). However, when stratified by age, these sex differences and differences in BSA (data not shown) were only observed in children aged 8-9 y.…”
Section: Discussionsupporting
confidence: 82%
“…The WHO has developed criteria for defining TGR in children based on BSA, age, and sex (16,19), whereas the criteria in China were according to age (5). In this study, the Tvol was slightly higher in boys than in girls which is consistent with other studies (10,32,33). However, when stratified by age, these sex differences and differences in BSA (data not shown) were only observed in children aged 8-9 y.…”
Section: Discussionsupporting
confidence: 82%
“…The thyroid gland increases in size as children grow, and some studies have suggested that there is no significant difference in thyroid volume between genders, and others stated that differences were seen post‐puberty . Age, sex and anthropometric characteristics such as body surface area (BSA), weight and height of individuals are positively associated with thyroid volume . Thyroid volume as a function of BSA takes into account the difference in body development between children of the same age especially in developing countries .…”
Section: Anthropometric Characteristicsmentioning
confidence: 99%
“…Objęli oni badaniem grupę 360 dzieci szkolnych w wieku 8-15 lat (59% stanowiły dziewczynki). Stwierdzono, że objętość tarczycy u dzieci objętych badaniem była mniejsza niż referencyjne wartości zaproponowane przez WHO [20].…”
Section: Dyskusjaunclassified